Non-contrast-enhanced 3-Tesla Magnetic Resonance Imaging Using Surface-coil and Sonography for Assessment of Hidradenitis Suppurativa Lesions - Fatemeh Jabbary Lak; Mona Mazinani; Johannes T. Heverhagen; Robert E. Hunger; Keivan Daneshvar; S. Morteza Seyed Jafari (Medical Journals Sweden, 2020)
Hidradenitis suppurativa has a substantial negative effect on quality of life of affected persons. Diagnosis is based mainly on clinical examination. However, physical examination alone might underestimate disease severity compared with imaging modalities. We report here the application of non-contrast-enhanced 3-Tesla magnetic resonance imaging using surface-coil and sonography for assessment of hidradenitis suppurativa lesions based on topographic assessment of skin lesions. In addition, we review the literature regarding the application of ultrasound and magnetic resonance imaging in hidradenitis suppurativa.